The role of peer review in identity development for engineering education researchers. (4th May 2019) - Gardner, Anne; Willey, Keith
ABSTRACT: Peer review has been the focus of an ongoing study at a series of recent annual conferences of the Australasian Association for Engineering Education (AAEE). A further development of this study has been to explore the perspective/s of the authors of these conference papers and the impact that peer review can have on their development as researchers. This paper uses the identity-trajectory framework to illustrate relationships between peer review and academic identity construction for engineering education authors in the AAEE community. Participants' responses illustrate how various aspects of responding to reviews and writing reviews for other authors, contribute to the development of the networking and intellectual strands of their academic identity as engineering education researchers. We suggest that members of the global engineering education community should be mindful of how they write their peer reviews of conference papers to ensure the opportunity to constructively contribute to their peers' successful transition into this different research paradigm is not missed.